The Effectiveness of RSI and MACD in Determining Buy and Sell Signals - Nurhikma Nurhikma; Wa Ode Rayyani (Penerbit Goodwood, 2026)
Purpose: This study analyzes the effectiveness of Relative Strength Index (RSI) and Moving Average Convergence Divergence (MACD) in generating buy and sell signals for five mining stocks on the Indonesia Stock Exchange.Methodology: This research uses a quantitative descriptive and verificative approach with secondary data consisting of daily historical prices and RSI, MACD, Signal Line, and Histogram values from the Indonesia Stock Exchange and TradingView. Results: Both RSI and MACD detected price reversal points, with differing accuracy and timing across the five stocks. RSI produced more frequent, earlier signals identifying overbought and oversold conditions, while MACD produced fewer but more reliable signals confirming medium term trend changes during periods of strong momentum.Conclusions: MACD is relatively more effective than RSI for determining buy and sell signals on mining stocks, generating more consistent signals during trending markets, while RSI performs better as a complementary indicator confirming overbought or oversold conditions before entry or exit. Limitations: This study is limited to five mining stocks and one period, relying only on RSI and MACD without other indicators, so findings may not generalize.Contributions: These findings offer practical insight for investors selecting technical indicators for entry and exit timing in the Indonesian mining sector, and an empirical basis for research combining technical and fundamental analysis.